Lipid A Biosynthesis of Multidrug-Resistant Pathogens - A Novel Drug Target - Lee, Chang-Ro; Hun Lee, Jung; Chul Jeong, Byeong; Hee Lee, Sang (Current Pharmaceutical Design, 2013)
The rapid increase of human infections by multidrug-resistant (MDR) Gram-negative pathogens poses a serious health threat and demands the identification of new strategies, molecular targets, and agents for the treatment of Gram-negative bacterial infections. The biosynthesis of lipid A, the membrane-anchoring portion of lipopolysaccharide (LPS), is one promising target for novel antibiotic design because lipid A is essential for LPS assembly in most Gram-negative bacteria. The first three enzymes in the biosynthesis of lipid A, UDP-N-acetylglucosamine acyltransferase (LpxA), UDP-3-O-(R-3-hydroxyacyl)-N-acetylglucosamine deacetylase (LpxC) and UDP- 3-O-(R-3-hydroxyacyl)glucosamine N-acyltransferase (LpxD), have emerged as an attractive Gram-negative antibacterial molecular target. In this article, we review recent advances in the studies on the structures and the structure-based drug designs of the three enzymes.
Keywords: acyltransferase